Homeschooling in America : capturing and assessing the movement - Murphy, Joseph, 1949- (Thousand Oaks, Calif. : Corwin Press, 2012)
Despite its expansion in recent years to two million students, homeschooling is the least understood component of American education. Preeminent educational scholar Joseph Murphy offers a revealing look at today's homeschooling movement. Policy makers, researchers, educators and homeschooling organizations will find answers to compelling Questions, including.
Includes bibliographical references (p. 161-178) and index.
Keywords: Home schooling -- United States -- History; Home schooling -- Social aspects -- United States